2018
DOI: 10.1016/j.physletb.2017.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Model-independent constraints on Lorentz invariance violation via the cosmographic approach

Abstract: Since Lorentz invariance plays an important role in modern physics, it is of interest to test the possible Lorentz invariance violation (LIV). The time-lag (the arrival time delay between light curves in different energy bands) of Gamma-ray bursts (GRBs) has been extensively used to this end. However, to our best knowledge, one or more particular cosmological models were assumed a priori in (almost) all of the relevant works in the literature. So, this makes the results on LIV in those works model-dependent an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 100 publications
1
16
0
Order By: Relevance
“…[119,120] extended this analysis to different cosmological models and showed that the result is insensitive to the adopted background cosmology. Subsequently, some cosmology-independent approaches were applied to probe the possible LIV effects [121,122].…”
Section: Present Resultsmentioning
confidence: 99%
“…[119,120] extended this analysis to different cosmological models and showed that the result is insensitive to the adopted background cosmology. Subsequently, some cosmology-independent approaches were applied to probe the possible LIV effects [121,122].…”
Section: Present Resultsmentioning
confidence: 99%
“…[66,67] extended this analysis to other different cosmological models, finding the result is only weakly sensitive to the background cosmology. Some cosmology-independent techniques were furthermore applied to this kind of analysis [68,69].…”
Section: Gamma-ray Burstsmentioning
confidence: 99%
“…for the massive photon. We will assume a ΛCDM cosmology to determine the Hubble parameter H(z); in general one should consider a variety of cosmological models [45][46][47][48], although this is beyond the scope of this work. In both cases we see that the parameter of interest (E QG or m γ ) and the observed energy bands appear as scaling factors.…”
Section: A Forward Modelling the Time Delaymentioning
confidence: 99%